Boehmeria nivea Attenuates the Development of Dextran Sulfate Sodium-Induced Experimental Colitis - Eun Ju Shin; Mi Jeong Sung; Hye Jeong Yang; Myung Sunny Kim; Jin-Taek Hwang (Mediators of Inflammation)
We examined the therapeutic effect of an ethanol extract derived from Boehmeria nivea (Linn.) Gaudich in a mouse model of experimental colitis. Treatment with 70% ethanol extract derived from B. nivea (EBN) at a dose of 100, 200, or 500 mg/(kg·d) improved colon shortening, body weight, the disease activity index (DAI), and histopathological score of DSS-induced colitis mice. DSS significantly increased the levels of cyclooxygenase-(COX-) 2 in colon tissue relative to that of the untreated control group. EBN administered at 100, 200, or 500 mg/(kg·d) reduced COX-2 levels in the DSS-treated mice. In addition, EBN decreased the DSS-induced secretion of the inflammatory cytokine interleukin-6 (IL-6) and chemokine monocyte chemotactic protein-1 (MCP-1). Taken together, these data suggest that B. nivea extract is effective in preventing colitis.